PENERAPAN RANGE OF MOTION (ROM) PASIF DALAM PEMENUHAN KEBUTUHAN MOBILITAS FISIK PADA PASIEN STROKE NON HEMORAGIK DI GADJAH MADA STROKE CENTER NAKULA 4 RS AKADEMIK UGM - Khristiyani , Khristiyani; Sugeng Jitowiyono (Jurnal Cakrawala Ilmiah, 2024)
Background: Non-Hemorrhagic Stroke is a type of stroke that occurs due to blockage in the blood vessels of the brain, the blood supply to the brain is disrupted resulting in impaired mobility. Individuals with movement disorders need mobilization exercises in the form of passive Range of Motion (ROM) exercises which aim to increase or maintain muscle flexibility and strength. Objective: To apply Passive Range of Motion (ROM) to the problem of impaired physical mobility in Non-Hemorrhagic Stroke patients at the Gadjah Mada Stroke Center Nakula 4 UGM Academic Hospital. Method: In writing this case study, the author used a descriptive method, describing the nursing process approach which includes the assessment stages, formulation of diagnoses, nursing planning, implementation, evaluation and documentation. Results: Assessment of Mrs. M and Mr. K shows that there is weakness in the right limb. Both patients showed the same nursing problem, namely impaired physical mobility. Nursing planning for physical mobility disorders by applying evidence based nursing practice passive Range of Motion (ROM) to increase muscle strength in patients. Nursing implementation is carried out by applying passive Range of Motion (ROM) to increase muscle strength which is carried out 2 times per day for approximately 15-20 minutes in 1 exercise. The nursing diagnosis evaluation obtained in both patients was the same, namely an increase in muscle strength. Conclusion: After the patient Mrs. M and Mr. K carried out passive Range of Motion (ROM) for the problem of impaired physical mobility in Non-Hemorrhagic Stroke patients at Gadjah Mada Stroke Center Nakula 4 UGM Academic Hospital can increase muscle strength in Non-Hemorrhagic Stroke patients.